Technology-based entrepreneurship enabling factors in higher education institutions with a limited entrepreneurial trajectory in Colombia - Benavides-Sánchez, Edward Andrés; Castro-Ruíz, Camilo Andrés; Quintero-Angel, Mauricio (Cuadernos de Administración, 2021)
Higher education institutions as Technology-Based Entrepreneurship Development Centers (TBE) are among the strategic bets to encourage the creation and consolidation of companies with a solid scientific-technological component. This study seeks to identify those factors enabling the promotion of a TBE culture in higher education institutions with limited experience in entrepreneurship in Colombia, based on a case study in Universidad del Valle’s (Colombia) regionalization system. The methodology applied the World Café technique on interdisciplinary group sessions with coordinators of Universidad del Valle - Palmira Campus - academic programs, who were asked about their perceptions regarding TBE and were also asked to identify strengths, weaknesses, opportunities, and threats under a collaborative work scheme, which were subjected to content analysis. The results prove that developing a TBE culture demands abundant resources, and the strategic leadership needs special strengthening to have TBE included in strategic and tactical planning and the goals and indicators set to allow monitoring over time. Likewise, institutional capabilities, budgeting, the qualification of human resources, investment in laboratories, and relationships with the actors in the entrepreneurial ecosystem need strengthening. Finally, the conclusion is drawn that TBE is an opportunity for the University-Company-State-Society articulation and the consolidation of companies that energize the business fabric and bring resources and recognition to higher education institutions.